NaFeTiO4: A novel visible light active photocatalyst for water splitting and environmental remediation - Shinde, Deepali S.; Bhange, Pallavi D.; Arbuj, Sudhir S.; Kim, Ji-Young; Bae, Jee Hwan; Nam, Kyung-Wan; Tayade, Shivaji N.; Bhange, Deu S. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Single phase, crystalline NaFeTiO4 with tunnel structure is prepared by a solid state method and explored as a novel photocatalyst for the first time. Structural, optical and morphological properties of NaFeTiO4 are investigated by various characterization techniques such as X-ray diffraction (XRD), scanning & transmission electron microscopy (SEM & TEM), Energy dispersive X-ray spectroscopy (EDS), N-2 adsorption-desorption study (BET), UV-vis, X-ray photoelectron, X-ray absorption (UV-vis DRS, XPS and XANES) and photo-luminescence (PL) spectroscopy. The interfacial charge transfer ability of the prepared ntype NaFeTiO4 was also investigated by transient photocurrent response and electro-chemical impedence spectroscopy which proved to be an efficient tool for better understanding of electronic properties of NaFeTiO4. The photocatalytic efficiency of NaFeTiO4 is evaluated for decomposition of methylene blue (MB) and Rhodamine B (RhB) dyes as well as for H-2 evolution through water splitting reaction under visible light. NaFeTiO4 exhibits efficient charge separation properties, excellent photocatalytic activities and reusability. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.